2010
DOI: 10.1099/vir.0.023598-0
|View full text |Cite
|
Sign up to set email alerts
|

Rinderpest virus expressing enhanced green fluorescent protein as a separate transcription unit retains pathogenicity for cattle

Abstract: A full-length DNA clone of a virulent strain of rinderpest virus was constructed with the gene for the enhanced green fluorescent protein (eGFP) inserted as a separate transcription unit between the P and M genes. Rescue of the virus from the modified clone using reverse genetics generated a virus that grew to the same levels as the virus rescued from the unmodified DNA clone in cell culture. The recombinant virus expressed eGFP to a high level and was used to follow virus replication in real-time using live-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To our knowledge, no recombinant PPRV harbouring an additional transcription unit (ATU) has been used in pathogenesis studies. Although it is known that adding an ATU (especially before the nucleoprotein, position 1) may alter the morbillivirus-typical transcriptional gradient and therefore potentially attenuate the recombinant virus [32], an in vivo study in cattle using recombinant RPV expressing EGFP on position 3 of the genome did not show any differences in pathogenesis compared to the virus without EGFP expression [47]. Moreover, in vitro characterization and comparison performed in this study did not hint towards any difference based on the insertion of EGFP in rPPRV/Tbilisi-EGFP, suggesting that the used virus strain and/or age of the animal were responsible for the moderate clinical symptoms observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no recombinant PPRV harbouring an additional transcription unit (ATU) has been used in pathogenesis studies. Although it is known that adding an ATU (especially before the nucleoprotein, position 1) may alter the morbillivirus-typical transcriptional gradient and therefore potentially attenuate the recombinant virus [32], an in vivo study in cattle using recombinant RPV expressing EGFP on position 3 of the genome did not show any differences in pathogenesis compared to the virus without EGFP expression [47]. Moreover, in vitro characterization and comparison performed in this study did not hint towards any difference based on the insertion of EGFP in rPPRV/Tbilisi-EGFP, suggesting that the used virus strain and/or age of the animal were responsible for the moderate clinical symptoms observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Growth curve analysis of recombinant rinderpest virus (RPVs) containing chimeric H proteins was conducted by Parida et al ( 2006 ) where Vero cells were infected with viruses such as RPV2C, PPRV, or RPV2C-PPRTm (at MOI 0.1) or virus RPV2C-PPRExt (at MOI 0.01), and the same titre was found on 72 hpi which was 3.5 log10 TCID 50 /ml. Marmoset B95a and Vero-SLAM cells were infected simultaneously with two rinderpest virus and titres were found between 5.0 log10 TCID 50 /ml and 6.0 log10 TCID 50 /ml by 96 hpi (Banyard et al 2010 ). In another study of rinderpest virus growth profile conducted by Nores and McCullough ( 1997 ) observed, the highest virus titres were obtained with the RPV-Saudi isolate at 10 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple paramyxoviruses expressing various fluorescent reporters have been used to gain insight into viral pathogenesis (Banyard et al, 2010; de Swart et al, 2007; de Vries et al, 2010; Ludlow et al, 2012; Rudd et al, 2006; von Messling et al, 2004), and a human metapneumovirus expressing green fluorescent protein (GFP) was used to evaluate the attenuating effect of altering N-glycosylation sites on various virus proteins both in vitro and in vivo for the development of live attenuated vaccines (Zhang et al, 2011). For Bornaviruses, dissemination throughout the nervous system was studied using a Borna disease virus expressing GFP (Ackermann et al, 2010).…”
Section: Applications Of Reporter-expressing Virusesmentioning
confidence: 99%